2020
DOI: 10.33969/jiec.2020.21007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Raising Switching Stages on the Reliability of Interconnection Networks

Abstract: Multistage Interconnection Networks (MINs) are a cost-effective idea for connection between different nodes in multi-processor systems. In the meantime, understanding the impact of increasing the number of stages (i.e. a famous method for improving fault tolerance) on the reliability of these networks is essential. Last studies on this challenging issue, revealed that adding one switching stage to MINs is preferable to two in terms of reliability. However, there were some non-negligible gaps in previous resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The authors in [58] studied the impact of increasing the number of switching stages on the reliability of SENs. They showed that SEN with an extra stage has higher reliability for small-scale systems in addition to its lower hardware cost.…”
Section: Recent Advancesmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors in [58] studied the impact of increasing the number of switching stages on the reliability of SENs. They showed that SEN with an extra stage has higher reliability for small-scale systems in addition to its lower hardware cost.…”
Section: Recent Advancesmentioning
confidence: 99%
“…In this section, we take some beneficial lessons towards making research advancements in the design of efficient interconnection networks from the literature (such as [2,3,7,21,35,58,[61][62][63][64][65][66][67][68]) and open up some new directions and guidelines.…”
Section: Future Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,[20][21][22][23][24][36][37][38][39]42 To meet such a challenging requirement of these super systems MIN are designed to behave as highly reliable and fault-tolerant interconnection networks. [25][26][27][28][33][34][35][36][37][44][45][46][47][48][49][50] Lot of researchers have paid attention in recent future to develop new designs of MIN which can withstand with multiple fault occurring in the network to provide reliable and pose free communication between processors and memories. [23][24][25][26][27][28][29]32,35,37 All designs of MINs proposed in last five years were centered around providing high fault tolerance by providing more redundant or alternative paths from each source to destination so as to bear more number of faults and providing dynamic rerouting scheme to reroute the packet to the destination through either backtracking or by activating alternative SE 1,[8][9][10][11][12][13]…”
mentioning
confidence: 99%